FORMATION OF MODERN AND PALEOZOIC STRATIFORM BARITE AT COLD METHANE SEEPS ON CONTINENTAL MARGINS - Torres M.E.; Bohrmann G.; Dubé T.E.; Poole F.G. (My University, 2003)
Stratiform (bedded) Paleozoic barite occurs as large conformable beds within organic- and chert-rich sediments; the beds lack major sulfide minerals and are the largest and most economically significant barite deposits in the geologic record. Existing models for the origin of bedded barite fail to explain all their characteristics: the deposits display properties consistent with an exhalative origin involving fluid ascent to the seafloor, but they lack appreciable polymetallic sulfide minerals and the corresponding strontium isotopic composition to support a hydrothermal vent source. A new mechanism of barite formation, along structurally controlled sites of cold fluid seepage in continental margins, involves barite remobilization in organic-rich, highly reducing sediments, transport of barium-rich fluids, and barite precipitation at cold methane seeps. The lithologic and depositional framework of Paleozoic and cold seep barite, as well as morphological, textural, and chemical characteristics of the deposits, and associations with chemosymbiotic fauna, all support a cold seep origin for stratiform Paleozoic barite. This understanding is highly relevant to paleoceanographic and paleotectonic studies, as well as to economic geology.
Keywords: barite; Paleozoic deposits; sulfur isotopes; chemosynthetic fossils; cold seeps; strontium isotopes; Paleozoic; Палеозой